Urine Trouble: Drug Testing of Students & Teachers in Public Schools - Frank Butler (Arizona State University, 2012)
Non-individualized (so-called "random") drug testing in public schools presents issues of Constitutional law on both the federal and state levels, particularly with regard to citizens' freedom from "unreasonable searches and seizures." The trend toward increasing acceptance of such testing by the courts (and particularly the U.S. Supreme Court) stands in tension with public-health approaches to preventing abuse of psychoactive substances. This paper analyzes the major legal, social, and ethical challenges presented by random drug-testing in schools.